Examining the Impact of Board of Directors on Sustainability Performance: The Role of Board Size and Meetings - Erlang Dwi Septian; Andrey Hasiholan Pulungan; Selfi Nurcholifah (ccounting Department, Universitas Syiah Kuala, Indonesia, 2025)
Sustainability performance is increasingly critical in Indonesia, highlighting the need for effective corporate governance through board size and meeting practices. This study examines the impact of board size and meeting frequency on sustainability performance. The population consists of energy sector companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. The sample comprises 77 companies, yielding 198 observations. Using multiple linear regression analysis, the results reveal that only board meeting frequency has a significant positive effect on sustainability performance, whereas board size has no significant influence. These findings are consistent with Resource Dependence Theory, suggesting that active and frequent board engagement enhances sustainability outcomes and strengthens shareholder trust.